Are molecular solvents, aqueous biphasic systems and deep eutectic solvents meaningful categories for liquid–liquid extraction? - Billard, Isabelle (Comptes Rendus. Chimie)
Two categories of so-called innovative liquid–liquid extraction systems have recently been added to the classic and well-established category of water/molecular solvent systems: aqueous biphasic systems (ABS) and hydrophobic deep eutectic solvents (DES). Each class displays properties that apparently distinguish it from the other two. However, these three classes seem to be irrelevant because the properties of mutual solubilities in these systems are identical in nature and can be easily understood via a simplified phase diagram. This unifying view is discussed in the light of systems representative of the three categories usually recognised. Two systems are well known in the literature of liquid/liquid extraction of metal ions: (i) H$_{2}$O/HNO$_{3}$/TBP, the archetype of the so-called classical liquid–liquid extraction (ii) H$_{2}$O/Na$_{2}$SO$_{4}$/PEG-4000, considered as an ABS. For the third system, H$_{2}$O/decanoic acid/N$_{4444}$Cl, presented as a hydrophobic DES by its discoverers, new experimental data have been acquired in this work.